Legal Aspects of Genetically Modified Food Product Safety for Health in Indonesia - abdullah khamdi (Jurnal Hukum dan Etika Kesehatan, 2022)
Genetic Engineering is the transplantation of one gene to another, both between genes and across genes, to produce valuable products for living beings. The rapid growth of genetic engineering in Indonesia and Genetically Modified (GM) food products has raised many worries and issues about these foods posing a health risk when consumed. Concerns about GM food products are increasing, including the possibility of allergic reactions, gene transfer, and outcrossing. Indonesia is one of the countries that has accepted the Cartagena Protocol, a security protocol designed to protect biodiversity from the potential risk posed by genetically modified organisms created by contemporary biotechnology. The writer, through this study, would like to convey the extent to which the existing regulations in Indonesia regarding GM food product safety for public health and how the government's responsibility in GM food product safety is for public health. As a result of this study, GM food products had been regulated by law, and the establishment of a Biosafety Commission was one form of government responsibility for preserving the safety of GM food products for public health.